Cystic Renal Oncocytoma and Tubulocystic Renal Cell Carcinoma: Morphologic and Immunohistochemical Comparative Study. Issue 2 (February 2016) - Skenderi, Faruk; Ulamec, Monika; Vranic, Semir; Bilalovic, Nurija; Peckova, Kvetoslava; Rotterova, Pavla; Kokoskova, Bohuslava; Trpkov, Kiril; Vesela, Pavla; Hora, Milan; Kalusova, Kristyna; Sperga, Maris; et al.
Abstract : Renal oncocytoma (RO) may present with a tubulocystic growth in 3% to 7% of cases, and in such cases its morphology may significantly overlap with tubulocystic renal cell carcinoma (TCRCC). We compared the morphologic and immunohistochemical characteristics of these tumors, aiming to clarify the differential diagnostic criteria, which facilitate the discrimination of RO from TCRCC. Twenty-four cystic ROs and 15 TCRCCs were selected and analyzed for: architectural growth patterns, stromal features, cytomorphology, ISUP nucleolar grade, necrosis, and mitotic activity. Immunohistochemical panel included various cytokeratins (AE1-AE3, OSCAR, CAM5.2, CK7), vimentin, CD10, CD117, AMACR, CA-IX, antimitochondrial antigen (MIA), EMA, and Ki-67. The presence of at least focal solid growth and islands of tumor cells interspersed with loose stroma, lower ISUP nucleolar grade, absence of necrosis, and absence of mitotic figures were strongly suggestive of a cystic RO. In contrast, the absence of solid and island growth patterns and presence of more compact, fibrous stroma, accompanied by higher ISUP nucleolar grade, focal necrosis, and mitotic figures were all associated with TCRCC. TCRCC marked more frequently for vimentin, CD10, AMACR, and CK7 and had a higher proliferative index by Ki-67 (>15%). CD117 was negative in 14/15 cases. One case was weakly CD117 reactive with cytoplasmic positivity. All cystic RO cases were strongly positive for CD117. The remaining markers (AE1-AE3, CAM5.2, OSCAR, CA-IX, MIA, EMA) were of limited utility. Presence of tumor cell islands and solid growth areas and the type of stroma may be major morphologic criteria in differentiating cystic RO from TCRCC. In difficult cases, or when a limited tissue precludes full morphologic assessment, immunohistochemical pattern of vimentin, CD10, CD117, AMACR, CK7, and Ki-67 could help in establishing the correct diagnosis.